Challenges and optimization ideas in low-power design for Internet of Things devices - Zhang, Jiulong; Yao, Linluo; Cui, Jinghua (International Journal of Advanced AI Applications, 2025)
This paper presents a systematic low-power optimization framework for Internet of Things (IoT) devices, aiming to address persistent energy consumption challenges in long-term deployments. By constructing a modular simulation model with four evaluation metrics—average power, response time, battery life, and task success rate—we compare baseline, hardware-only, and collaborative software-hardware strategies. Results show the proposed approach reduces average power to 7.9mW, extends battery life to 158.6 hours, and achieves a 97.2% task completion rate. Field deployment confirms its adaptability and reliability. The framework provides a practical and scalable solution for low-power IoT design.